Consumption Trends of Antifungal and Antiprotozoal Agents for Human Systemic Use in Kazakhstan from 2017 to 2023 - Yuliya Semenova; Assiya Kussainova; Laura Kassym; Ainur Aimurziyeva; Daniil Semenov; Lisa Lim (Antibiotics)
Background/Objectives: While multiple studies have investigated antibiotic consumption rates, there are few studies on the consumption of systemic antifungals and antiprotozoals. This study aims to fill this gap by providing a comprehensive analysis of nationwide consumption trends in Kazakhstan over a seven-year period (2017–2023). Methods: Defined daily doses per 1000 inhabitants per day were calculated for systemic antifungals (J02 code of the Anatomical Therapeutic Chemical Classification System (ATC)) and antiprotozoals (P01 code of the ATC). Time series analyses were applied to examine historical trends, evaluate the impact of the COVID-19 pandemic, and make future projections until 2030. Results: The total consumption increased over the study period, with an average annual percent change of 1.11% for antifungals and 5.48% for antiprotozoals. Fluconazole was the most consumed antifungal agent, whereas metronidazole was the most consumed antiprotozoal agent. The COVID-19 pandemic had a positive but insignificant effect on the consumption of antifungals and a negative and also insignificant effect on the consumption of antiprotozoals. Forecast modeling indicates that the future trends in antifungal and antiprotozoal consumption until 2030 will largely remain stable, with the exception of antiprotozoal consumption in the hospital sector, which is projected to decline. Conclusions: These findings offer valuable insights into the development and implementation of targeted antimicrobial stewardship programs in Kazakhstan.